Strategy of Theatre: an investigation into the Birmingham Repertory Theatre’s strategy for change and the future - Taylor, Johanna (2016)
This study is a case study of The Birmingham Repertory Theatre, “one of Britain’s leading producing theatres” (Birmingham Repertory Theatre, 2015). The main focus of this dissertation is to investigate Birmingham Repertory Theatre’s strategy for change and the future by looking specifically at their funding diversification strategies and the large scale move that they undertook from 2011-2013. In addition, how they utilise their dynamic capabilities to create an organisation with sustained long-term competitive advantage and success potential. The resource dependency theory was used to help understand the relationship that the theatre has with its external environment and funders. Historically, they have relied heavily on external funding but as there is less public money available for arts and culture in England it is necessary to develop an income diversification strategy that incorporates commercial income generation activities. This paper will investigate the potential effects of this change in funding strategy on the theatre’s core mission. The dynamic capabilities framework was also applied to the organisation in order to understand the theatre’s ability to survive in a changing environment while other arts businesses have failed. The primary research was collected through the use of one-to-one semi-structured interviews as part of a case study design. The participants were all members of the senior management team at Birmingham Repertory Theatre and were chosen because they would be able to provide insight into the strategic decision making processes. As a result of these interviews it was found that the theatre has diversified their income strategy by investing in their commercial team that sells spaces and manages corporate events within the building. The theory would suggest that for a charitable organisation such as this, to carry out commercial activities there may be some evidence of mission drift in which they lose sight of their core mission. However, the research showed that there was little concern of mission drift from the senior management team however the challenges lay within perceived loyalty of the organisation to the core mission by members of staff that are not part of the commercial team. This has the potential of affecting their intangible resources. The theatre manages to maintain and develop their dynamic capabilities through the use of an organic organisational structure while using an intuitive process to regularly search for new opportunities within the markets that they operate. This allows them to remain responsive and flexible to unexpected changes; to be able to exploit new opportunities and to reconfigure their resources easily. It has been recommended that the Birmingham Repertory Theatre consider applying the scenario planning method to proactively prepare for the future. This would allow the theatre an opportunity to consider and plan for a variety of possible futures.